KICHIK MAKTAB YOSHI BOLALARI EMOTSIONAL SOHASINI O’RGANISHNING ZARURIYATI - To’ychiyeva, Sh.J. (SCIENCE and SOCIETY, 2022)
Thisarticleexplains the need to study the emotional sphere of small school-age children as a problem. The pycholigical basis of emotional characteristics is covered. The relevance is explained. The features of the small school goshi are taken into account.
Keywords: communication; desire; emotional matrix; development factor